Odpowiedzi

2010-01-25T15:38:45+01:00
A)
(-7/12)+3/8= -14/24 + 9/24 = -5/24
b)
(-3 1/5- 2 1/2= -3,2 - 2,5 = -5,7
c)
1 1/6 -(-2 1/12)= -7/6 + 25/12 = -14/12 + 25/12 = 11/12
d)
3,7 -4 2/5= 3,7 - 4,4 = -0,7
e)
-7/8 +(0,7)= -7/8 + 7/10 = -70/80 + 56/80 = -14/80 = -7/40
f)
1,4-(-1 3/4= 1,4 + 1,75 = 3,15
h)
(2 1/6-(-1,6)= 13/6 + 1/6 = 14/6 = 2⅓
2010-01-25T15:39:45+01:00
(-7/12)+3/8= (-14/24)+9/24=-5/24
(-3 1/5 - 2 1/2=-16/5 - 5/2 = - 32/10 - 25/10=-57/10
1 1/6 -(-2 1/12)= 7/6-(-25/12)= 14/12 +25/12=39/12
3,7-4 2/5 = 3 7/10 - 4 4/10 = 37/10-44/10=-7/10
-7/8 +0,7 = -7/8 + 7/10= -70/80 + 56/80=-14/80
1,4 -(-1 3/4)= 1 4/10 - (- 7/4)= 14/10 + 7/4 = 56/40 + 70/40 =126/40
2 1/6 -(-1,6)= 13/6 + 1 6/10= 13/6 + 16/10 = 130/60 + 96/60=226/60